Association between microalbuminuria and outcome of non-diabetic population aged 40 years and over: The reaction study. Issue 4 (August 2020) - Xie, Qian; Xu, Chaoran; Wan, Qin
Highlights: MAU was associated with age, fasting plasma glucose, 2-h glucose, hemoglobin A1c, and triglycerides. Follow-up FBG, 2hPG, TG, and HbA1c levels in the IGR + MAU group were higher than those in other groups. MAU is a risk factor of the advancement of prediabetes to diabetes. The information collected can serve as a future prevent tool for diabetes morbidities. Abstract: Aims: The goal of this study was to analyze the association between microalbuminuria (MAU) and the outcome of non-diabetic populations among Chinese people. Methods: A cohort of 2042 Chinese individuals without diabetes, aged 40 years or older were included. We identified people with impaired fasting glucose and/or impaired glucose tolerance by conducting an oral glucose tolerance test, and then followed them up after 3 years. We defined MAU as a urinary albumin-to-creatinine ratio (ACR) exceeding the normal range of 2.5−25 mg/mmol (males) or 3.5−35 mg/mmol (females). Results: Among 2042 adults aged 40 years or older in an urban fringe area of Luzhou city (1984 cases were followed up), 262 (12.8%) developed diabetes over 3 years. MAU was significantly associated with age, fasting plasma glucose, 2-h glucose, hemoglobin A1c, and triglycerides (P < 0.05). Follow-up FBG, 2hPG, TG, and HbA1c levels in the IGR + MAU group were higher than those in other groups (P < 0.05). If the relative risk of the isolated normal glucose tolerance (NGT) group progressing to diabetes was set to 1, the risk of progression to diabetes in the NGT + MAU, isolated impaired glucose regulation (IGR), and IGR + MAU groups increased 1.1, 3.9, and 7.5 times, respectively. Conclusions: Our study found that MAU is associated with increased risk of diabetes in NGT and IGR populations, especially in the IGR populations, MAU may predict adulthood at very high risk for diabetes.